Peran Evaluasi Ranah Psikomotorik dalam Meningkatkan Keterampilan Tingkat Tinggi pada Pembelajaran PAI di SMA Muhammadiyah 2 Gemolong - Wahid Ahmad Al-Qodri; Abdan Rafi’i; Tegar Mu’ammar Kadafi; Amar Khoir Afrizal Pratama Putra; Umar Hakam Alfaruq; Nurul Latifatul Inayati (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This study investigates how psychomotor domain evaluation contributes to enhancing high-level skills in Islamic Religious Education (PAI) at SMA Muhammadiyah 2 Gemolong. Psychomotor evaluation, encompassing physical skills and activities, plays a vital role in helping students understand religious principles theoretically and apply them in daily life. Observation, interviews, and documentation served as the primary tools in this qualitative and descriptive research. The findings reveal that psychomotor evaluation aids students in developing Islamic skills such as critical thinking, problem-solving, and decision-making. Students also benefit from evaluation methods like observation, practice tests, and simulations. This study is expected to provide practical recommendations for improving the quality of PAI learning and establishing a comprehensive evaluation system. Furthermore, it aims to assist teachers in shaping students with both academic competence and practical skills.